Child abuse: a painful reality behind closed doors - NU. CEPAL (ECLAC, 2014)
Child abuse violates the most basic rights of children and adolescents. As documented in the main article of this issue of Challenges, child abuse is a massive, daily and underreported problem that affects the population of Latin America and the Caribbean. It manifests itself in different forms, including physical and psychological aggression, rape and sexual abuse, and takes place in the home, in neighbourhoods, at school, at work and in legal and child protection institutions. Abuse tends to be transmitted from one generation to the next, and the individuals most often responsible are parents or other adult members of the household